Mebel Multifungsi Portable untuk Makeup Artist - Onny Julian Wibowo (Intra, 2017)
The world of makeup is increasingly in demand by various circles ranging from teenagers to adults, women and men. Work as a makeup artist is also growing rapidly. More and more people who work as a makeup artist is also offset by the increasing number of users of their services. In general, the profession as a makeup artist requires high flexibility and mobility. They are required to work on time and move a lot for both domestically and abroad. In addition, the equipment that they bring is expensive and requires special treatment and care. This condition requires makeup artists to have a work field that can fulfill and facilitate their work. The design of this portable multifunctional furniture is expected to meet all the needs and support the makeup activities. The design concept of "Multi-flexibility in Simplicity" focuses on the fulfillment of furniture function value for flexibility packaged in a simple form. Designed furniture will be easy to carry and meet all the needs of the work of makeup artists.